STRATEGI PEMBIAYAAN PENDIDIKAN PADA SDIT IMAM SYAFI’I MENJADI SEKOLAH FAVORIT - Nurhakim Waras; Fiki Naoval; Hafid Irham (STIT TANGGAMUS, 2022)
Strategy is an individual or group effort to create a scheme in order to achieve the intended targets. achieve the expected goals. Included in the strategy of raising funds for financing education at SDIT Imam Syafi'iPetanahan. Education financing is often considered to be the main problem to encourage private schools to become excellent schools. This study wants to examine the education financing strategy carried out by one of the leading schools. The study is based on a case study of SDIT Imam Syafi'iPetanahan. This study found an educational financing model that was able to make SDIT Imam Syafi'iPetanahan become a favorite school among the Petanahan community in particular, and the Kebumen community in general. Based on this school's experience, parental participation in education financing must be balanced by providing quality assurance to education consumers.